A kind of foamed copper material and preparation method and its application as automobile cushion material
Patent Information
- Application Number
- CN202510933549.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-08
- Publication Date
- 2026-08-28
- Estimated Expiration
- 2045-07-08
AI Technical Summary
现有技术中并没有使用溶体发泡法制备泡沫铜的方法,究其原因,目前熔体发泡法最常使用的发泡剂TiH2的起始分解温度为:400~450℃,剧烈分解温度:500~600℃
[0028]本发明克服了现有技术的难题,调整材料配方以及配比,使用溶体发泡法制备得到了泡沫铜产品,且该产品具有硬度大,韧性强的特点,具有优异的缓冲性能、阻燃性能、吸音性能和散热功能。
Smart Images

Figure CN120624884B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new materials technology, and in particular relates to a foamed copper material, its preparation method, and its application as an automotive cushioning material. Background Technology
[0002] As typical porous metal materials, aluminum foam and copper foam have become key materials in high-end fields such as military, aerospace, and transportation due to their high porosity, low density, and multifunctional properties such as sound absorption, vibration reduction, and electromagnetic shielding.
[0003] Currently, China and other developed countries have made significant progress in automobile manufacturing and innovation, but safety hazards have not yet been effectively addressed. Therefore, solving automobile safety issues is an urgent problem to be solved.
[0004] Modern cars may differ in design, but their basic structure is similar. The front and rear bumper beams are made of cold-rolled steel sheets (approximately 1.5 to 2.5 mm thick) or aluminum alloy and are fixed to the main beam structure of the lower body shell in an irregular shape. They are filled with plastic foam or other low-cost materials and designed to be shaped. Their purpose is to dissipate heat and enhance the appearance of the car, but their impact protection function is relatively weak.
[0005] The main methods for preparing copper foam are infiltration casting, powder metallurgy, and electrodeposition sintering. For large-scale production, electrodeposition and powder metallurgy are more commonly used. Currently, there is no method for preparing copper foam using melt foaming. The reason for this is that the most commonly used foaming agent in melt foaming, TiH2, has an initial decomposition temperature of 400-450℃ and a violent decomposition temperature of 500-600℃.
[0006] Copper has a melting point of 1083.4℃, which is much higher than the decomposition temperature of TiH2. If TiH2 is used for foaming, it will decompose rapidly and uncontrollably the moment it is added to the copper melt during the foaming process. This means that TiH2 does not have enough time to play its foaming role in the copper melt, and therefore, foamed copper products cannot be obtained.
[0007] Therefore, existing technologies for preparing copper foam utilize powder metallurgy, deposition, and casting methods. However, these methods are complex, costly, and some are environmentally unfriendly. For example, Chinese patent CN200710066 393.6 discloses a method for preparing through-hole copper foam, Chinese patent CN201010105738.6 discloses a method for preparing ultrafine copper foam using complexes, and Chinese patent CN201110116539.X discloses a process for preparing copper foam profiles. These methods require sophisticated equipment, are costly, and involve complex processes. Therefore, there is an urgent need for a simple, low-cost, easy-to-operate, and industrially viable process for preparing copper foam, enabling the low-cost, large-scale application of the produced copper foam in automotive anti-collision devices. Summary of the Invention
[0008] The purpose of this invention is to provide a foamed copper material and its preparation method, as well as its application as an automotive cushioning material, to ensure automotive safety.
[0009] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0010] An application of foamed copper, wherein the foamed copper is used to manufacture automotive cushioning materials, the cushioning materials being used for automotive anti-collision beams and the linings of the A-pillar, B-pillar, and C-pillar of the vehicle body.
[0011] As a limitation of the present invention, the foamed copper is cut and engraved into a shape that fits the inner cavity of the main beam of the front and rear anti-collision beams of automobiles and is disposed therein.
[0012] As a further limitation of the present invention, the foamed copper is cut and carved into a shape that fits the internal cavity of the A-pillar, B-pillar, and C-pillar of the car body and is disposed in the cavity.
[0013] As a further limitation of the present invention, the energy-absorbing boxes of the front and rear anti-collision beams of the automobile are filled with copper foam material.
[0014] The foamed copper material provided in this invention has the following chemical composition and weight percentage: Cu 90.0-93.0%; Al 2.5-3.50%; Fe 2.85-4.75%; Ni 0.036-0.125%; C 0.075-0.175%; Si 0.021-0.06%; S 0.0015-0.0025%; P 0.00045-0.0015%.
[0015] As a limitation of the present invention, the porosity of the copper foam is 78% to 90%, and the density is 0.25 g / cm³. 3 ~0.6g / cm 3 .
[0016] Another object of the present invention is to provide a method for preparing copper foam, comprising the following steps:
[0017] Step A: Prepare raw materials, including copper blocks, low-nickel cast iron blocks, and aluminum blocks;
[0018] Step B: Heat the copper block until it melts;
[0019] Step C: Add the low-nickel cast iron block to the molten copper from Step B and stir until melted;
[0020] Step D: Add the aluminum block to the molten mixture from Step C, stir until the aluminum block melts, and then cool down;
[0021] Step E: Add foaming agent to the molten liquid from step D and stir, then transfer it to a foaming tank and let it stand for foaming.
[0022] Step F: Cool and solidify at room temperature to obtain the product, copper foam.
[0023] As a limitation of the present invention, the mass percentage of each raw material in step A is 90-93% copper block, 3-5% low-nickel cast iron block, and 2.5-3.5% aluminum block, wherein the copper block is selected from scrap copper or brass.
[0024] This application creatively utilizes low-nickel cast iron blocks. The high carbon content in low-nickel cast iron lowers its melting point, making it very close to that of copper. Furthermore, carbon plays a role in the mutual solubility of other elements in the alloy, thus increasing its strength within the alloy foam. The presence of silicon primarily facilitates material cutting during processing. The presence of sulfur and phosphorus allows the sponge copper to act as a binder during the buffering process, achieving a more effective cushioning effect. Nickel (Ni) is a hard and ductile non-ferrous metal with a melting point of approximately 1450 degrees Celsius. In a high-carbon composition, its melting point can be lowered by about 100 degrees Celsius. Another key property is its high polishability and corrosion resistance. The addition of aluminum blocks also lowers the temperature of the molten copper alloy.
[0025] As a further limitation of the present invention, the composition and percentage of the low-nickel cast iron block are Fe 94.5-95.5%; Ni 1.2-2.5%; C 2.5-3.5%; Si 0.7-1.2%; S 0.04-0.06%; P 0.015-0.03%.
[0026] As a further limitation of the present invention, in step A, the copper block is heated to 1250-1300°C, and in step D, it is cooled to 900-1000°C. The low-nickel cast iron block and aluminum block are crushed into powder before being added, and the mixture is vigorously stirred in steps C and D.
[0027] By adopting the above-described technical solution, the beneficial effects achieved by this invention compared to the prior art are as follows:
[0028] This invention overcomes the difficulties of the prior art by adjusting the material formula and ratio, and using the melt foaming method to prepare foamed copper products. These products have the characteristics of high hardness and high toughness, and have excellent cushioning performance, flame retardant performance, sound absorption performance and heat dissipation function.
[0029] The auxiliary alloy of this invention absorbs energy at its original liquid temperature (approximately 1250-1300 degrees Celsius) and dissolves in the main liquid within a short time. This allows the copper-based alloy liquid to remain in a liquid state even at temperatures nearly 150 degrees Celsius below the melting point of copper. Therefore, it overcomes the difficulties of existing technologies and allows for the preparation of foamed copper using a solution foaming method. The strength of the prepared foamed copper is more than 2.5 times that of foamed aluminum.
[0030] The foamed copper material of this invention can be used to manufacture the front and rear anti-collision beams of automobiles, as well as the A-pillars, B-pillars, and C-pillars. It can be used to create infill material models or partial models of the original car model, that is, to replace the materials on the front and rear anti-collision beams and the left and right A-pillars, B-pillars, and C-pillars of the car body with the foamed copper of this application. This does not affect the appearance of the car body, nor does it occupy the interior space of the car. By using the principle of overcoming rigidity with flexibility, and with the same size, it replaces the plastic foam anti-collision blocks and other materials installed on the front and rear anti-collision beams and the A, B, and C pillars of the car, which can significantly improve the car's buffering capacity when it is hit, and ensure people's safety.
[0031] In summary, the method for preparing copper foam provided by this invention is simple and easy to implement, suitable for industrial production, and reduces production costs. The prepared copper foam material exhibits excellent performance, high strength, and high toughness, and can be used in the automotive industry to improve its crashworthiness and ensure life safety. Attached Figure Description
[0032] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.
[0033] Figure 1 This is an image of the foamed copper sheet prepared in Example 1;
[0034] Figure 2 This is a schematic diagram of the application of the foamed copper material of this application in automobiles.
[0035] In the diagram: 1. Front bumper beam; 2. Rear bumper beam; 3. A-pillar; 4. B-pillar; 5. C-pillar. Detailed Implementation
[0036] The preferred embodiments of the present invention will be described below with reference to the accompanying drawings. It should be understood that the preferred embodiments described herein are for illustrative and understanding purposes only and are not intended to limit the scope of the invention.
[0037] Example 1
[0038] like Figure 2As shown, the foamed copper material prepared in this application is cut and engraved to obtain the front anti-collision beam 1, rear anti-collision beam 2, and the inner linings of A-pillar 3, B-pillar 4, and C-pillar 5 of a car according to the shape of different car anti-collision beams. That is, the foamed copper material is prepared into the shape of the inner cavity of the main beam of the car anti-collision beam and is used as a filling material to fill the inner cavity of the main beam. According to the shape of A-pillar 3, B-pillar 4, and C-pillar 5 of different cars, the foamed copper material is cut and engraved to obtain the shape that fits the inner cavity of A-pillar 3, B-pillar 4, and C-pillar 5 and is applied thereto.
[0039] It can also be used to prepare the internal filling material for the energy-absorbing boxes of the front bumper beam 1 and the rear bumper beam 2. In the event of an accident, such as a collision between two vehicles or a vehicle hitting a wall, the front bumper beam 1 and the rear bumper beam 2 can play a buffering role. If the vehicle is hit from the side, the A-pillar 3, B-pillar 4, and C-pillar 5 can play a buffering role, greatly protecting the occupants of the vehicle.
[0040] Example 2
[0041] A method for preparing copper foam includes the following steps:
[0042] Step A: Prepare raw materials, including copper blocks, low-nickel cast iron blocks, and aluminum blocks; the composition is 93% copper blocks, 3.5% low-nickel cast iron blocks, and 3.5% aluminum blocks. The copper blocks are selected from scrap brass. The composition and percentage of the low-nickel cast iron blocks are: Fe 94.5-95.5%; Ni 1.2-2.5%; C 2.5-3.5%; Si 0.7-1.2%; S 0.04-0.06%; P 0.015-0.03%.
[0043] Step B: Heat the copper block to 1250℃ using a medium-frequency furnace until it melts and becomes fluid;
[0044] Step C: Add the low-nickel cast iron block to the molten copper liquid in step B and stir until melted. The low-nickel cast iron block should be crushed into powder beforehand and stirred vigorously after being added.
[0045] Step D: Add the aluminum block to the molten mixture from Step C. Crush the aluminum block into powder beforehand, stir vigorously until melted, and then rapidly cool to 1000℃.
[0046] Step E: Add foaming agent to the molten liquid in step D and stir rapidly. Then, transfer the melt to a foaming tank and let it stand to foam.
[0047] Step F: Cool and solidify at room temperature to obtain the product, copper foam.
[0048] like Figure 1 The image shown is of the cut foamed copper, which reveals that the internal pore structure of the material is relatively uniform.
[0049] Example 3
[0050] A method for preparing copper foam includes the following steps:
[0051] Step A: Prepare raw materials, including copper blocks, low-nickel cast iron blocks, and aluminum blocks; the composition is 92% copper blocks, 5% low-nickel cast iron blocks, and 3% aluminum blocks. The copper blocks are selected from scrap copper. The composition and percentage of the low-nickel cast iron blocks are: Fe 94.5-95.5%; Ni 1.2-2.5%; C 2.5-3.5%; Si 0.7-1.2%; S 0.04-0.06%; P 0.015-0.03%.
[0052] Step B: Heat the copper block to 1300℃ in a medium-frequency furnace until it reaches a molten state, which is then ready to flow.
[0053] Step C: Add the low-nickel cast iron block to the molten copper liquid in step B and stir until melted. The low-nickel cast iron block should be crushed into powder beforehand and stirred vigorously after being added.
[0054] Step D: Add the aluminum block to the molten mixture from Step C. Crush the aluminum block into powder beforehand, stir vigorously until melted, and then rapidly cool to 900°C.
[0055] Step E: Add foaming agent to the molten liquid from step D and stir rapidly. Transfer the melt to a foaming tank and let it stand to foam.
[0056] Step F: Cool and solidify at room temperature to obtain the product, copper foam.
[0057] Example 4
[0058] A method for preparing copper foam includes the following steps:
[0059] Step A: Prepare raw materials, including copper blocks, low-nickel cast iron blocks, and aluminum blocks; the copper blocks are 92%, the low-nickel cast iron blocks are 4.5%, and the aluminum blocks are 3.5%. The copper blocks are selected from scrap copper. The composition and percentage of the low-nickel cast iron blocks are: Fe 94.5-95.5%; Ni 1.2-2.5%; C 2.5-3.5%; Si 0.7-1.2%; S 0.04-0.06%; P 0.015-0.03%.
[0060] Step B: Heat the copper block to 1300℃ in a medium-frequency furnace until it reaches a molten, flowing state;
[0061] Step C: Add the low-nickel cast iron block to the molten copper liquid in step B and stir until melted. The low-nickel cast iron block should be crushed into powder beforehand and stirred vigorously after being added.
[0062] Step D: Add the aluminum block to the molten mixture from Step C. Crush the aluminum block into powder beforehand, stir vigorously until melted, and then rapidly cool to 950°C.
[0063] Step E: Add foaming agent to the molten liquid from step D and stir rapidly. Transfer the melt to a foaming tank and let it stand to foam.
[0064] Step F: Cool and solidify at room temperature to obtain the product, copper foam.
[0065] The titanium hydride foaming agent used in the embodiments and comparative examples of this application is obtained by the preparation method of patent CN202411437366.5, which can effectively foam at a high temperature of 1000 degrees Celsius.
[0066] The copper foam materials prepared in Examples 2-4 were tested.
[0067] Experiment Example 1 – Porosity Experiment
[0068] The porosity of copper foam was measured using the water displacement method. Regularly shaped copper foam materials were cut, and the mass of the copper matrix was first weighed. The volume was calculated using the density formula. The prepared copper foam sample was wrapped in plastic wrap or other waterproof material and placed in a beaker, ensuring the sample was completely submerged below the water level. The volume of the copper foam sample was obtained by subtracting the beaker's initial reading before the sample was placed from the reading aligned with the water level. The porosity of the copper foam could then be calculated using the following formula:
[0069]
[0070] Where P--- is the porosity of the copper foam sample;
[0071] ρ --- density of the copper matrix;
[0072] ρ0 --- Density of the copper foam sample;
[0073] V --- Total volume of the copper substrate;
[0074] V0 --- Total volume of the copper foam sample;
[0075] The copper matrix sample was obtained by melting copper blocks, low-nickel cast iron and aluminum together during the preparation of foamed copper, and then cooling the mixture in a regular mold.
[0076] Example 2 87% 1.0 Example 3 90% 0.77 Example 4 84% 1.23
[0077] Experimental Example 2 – Measurement of Specific Strength
[0078] The instrument used is a universal testing machine. The specimen is cut into a standard tensile specimen and stretched at a constant rate until it breaks.
[0079]
[0080] Example 2 14.8 Example 3 14.5 Example 4 15
[0081] Experiment Example 3 – Bending Strength Test
[0082] A three-point bending test was conducted using a universal testing machine. The specimen was cut into a rectangle, and a load was applied at a constant rate. The load-displacement curve was recorded. The test was stopped when the specimen fractured, and the maximum load Fmax was recorded.
[0083] Calculation formula:
[0084] Where b is the sample width and h is the sample thickness, and b and h are multiplied by (1 − porosity) in the formula.
[0085] L is the span between the two support rollers.
[0086] After testing, the flexural strengths of Examples 2-4 were 48, 52, and 55 MPa, respectively.
[0087] The above experiments show that the foamed copper material prepared in this application has a relatively uniform internal pore structure and excellent specific strength and bending strength. It is suitable as a buffer material for automobiles, filling the front and rear anti-collision beams, as well as the A, B, and C pillars, to significantly improve the vehicle's anti-collision performance and play an excellent buffering role.
[0088] It should be noted that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art can still modify the technical solutions described in the above embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A type of foamed copper, characterized in that: The chemical composition and weight percentage of the material are as follows: Cu 90.0~93.0%; Al 2.5~3.50%; Fe 2.85~4.75%; Ni 0.036~0.125%; C 0.075~0.175%; Si 0.021~0.06%; S 0.0015~0.0025%; P 0.00045~0.0015%.
2. The foamed copper according to claim 1, characterized in that: The porosity of the copper foam is 84%–90%, and its density is 0.77 g / cm³. 3 ~1.23g / cm 3 .
3. A method for preparing copper foam, characterized in that: A method for preparing a copper foam according to claim 1 or 2 includes the following steps: Step A: Prepare raw materials, including copper blocks, low-nickel cast iron blocks, and aluminum blocks; the mass percentage of each raw material is as follows: copper blocks 90-93%, low-nickel cast iron blocks 3-5%, and aluminum blocks 2.5-3.5%; the composition and percentage of the low-nickel cast iron blocks are: Fe 94.5-95.5%; Ni 1.2-2.5%; C 2.5-3.5%; Si 0.7-1.2%; S 0.04-0.06%; P 0.015-0.03%. Step B: Heat the copper block until it melts; Step C: Add the low-nickel cast iron block to the molten copper from Step B and stir until melted; Step D: Add the aluminum block to the molten mixture from Step C, stir until the aluminum block melts, and then cool down; Step E: Add foaming agent to the molten liquid from step D and stir, then transfer it to a foaming tank and let it stand for foaming. Step F: Cool and solidify at room temperature to obtain the product, copper foam.
4. The method for preparing copper foam according to claim 3, characterized in that: In step A, the copper block is selected from scrap copper or brass.
5. The method for preparing copper foam according to claim 3, characterized in that: In step A, the copper block is heated to 1250-1300℃, and in step D, it is cooled to 900-1000℃. The low-nickel cast iron block and aluminum block are crushed into powder before being added. After adding the materials in steps C and D, they are stirred rapidly.
Citation Information
Patent Citations
Through-hole foam copper preparation method
CN100569973C
Method for preparing superfine foam copper by coordination compound
CN101781724A
Preparation process of foamy copper section material
CN102443715A
Production system and preparation method of titanium hydride
CN119386763A
Copper-based composite foam material
CN111088443A